1996
DOI: 10.1139/v96-037
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield of singlet dioxygen and elucidation of the quenching mechanism for the reaction between the doublet excited states of tris(bipyridine)chromium(III) and triplet dioxygen

Abstract: Abstract:The formation of singlet dioxygen (lo2) in the reaction between the doublet excited states of tris(bipyridine)chromium(III) and triplet dioxygen in deuterium oxide was detected using near-infrared luminescence corresponding to singlet dioxygen decay. In addition, luminescence intensity measurements were used to determine the quantum yield of singlet dioxygen produced. A value of 0.86 ? 0.08 was obtained for the yield of lo2. Based on these quantum yield measurements, it is proposed that the major quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…This difference is consistent with minimal photocatalyst turnover for each, but with Ru serving as an initiator for a radical chain (with a radical chain length of roughly 50), whereas Cr only produces approximately stoichiometric product . Reported 3 O 2 quenching rates for excited states in the related complexes [Ru­(bpy) 3 ] 2+ and [Cr­(bpy) 3 ] 3+ are 6.8 × 10 8 and 2.5 × 10 7 M –1 s –1 , respectively, in acetonitrile. , Wrighton and Markham have reported competitive oxygen and aryl alkene quenching in Ru-based systems, , comparable to our observation of competitive quenching by dienophile and oxygen in a Cr-based system. In general, for each photophysical process Ru is faster and/or has a shorter lifetime than the Cr complex studied here.…”
Section: Discussionsupporting
confidence: 57%
“…This difference is consistent with minimal photocatalyst turnover for each, but with Ru serving as an initiator for a radical chain (with a radical chain length of roughly 50), whereas Cr only produces approximately stoichiometric product . Reported 3 O 2 quenching rates for excited states in the related complexes [Ru­(bpy) 3 ] 2+ and [Cr­(bpy) 3 ] 3+ are 6.8 × 10 8 and 2.5 × 10 7 M –1 s –1 , respectively, in acetonitrile. , Wrighton and Markham have reported competitive oxygen and aryl alkene quenching in Ru-based systems, , comparable to our observation of competitive quenching by dienophile and oxygen in a Cr-based system. In general, for each photophysical process Ru is faster and/or has a shorter lifetime than the Cr complex studied here.…”
Section: Discussionsupporting
confidence: 57%
“…Complexes of the form (NN)Pt(II)(SS), where N Ã/N0/bipyridine and 4,4?-ditert-butyl-2,2?-bipyridine, and S Ã/S0/3,4-toluenedithiolate (tdt), meso -1,2-diphenyl-1,2-ethanedithiolate or 1,2-ethanedithiolate produce singlet oxygen with moderate efficiency [43]. In these complexes, the fraction of triplet states quenched by oxygen ranged from 0.11 to 0.20.…”
Section: 'mentioning
confidence: 99%
“…Acetylacetonato complexes of Cr(III) are similarly effective photocatalysts for the oxygenation of α-pinene. The quantum yield of singlet oxygen generated in quenching of Cr(bpy) 3 3+ by molecular oxygen has recently been measured as 0.86, a greater efficiency than that for the popular oxygen-sensitizer Rose Bengal (φ = 0.80). The authors concluded that in the other 14% of quenching events, spin-catalyzed conversion to the ground states of Cr(bpy) 3 3+ and oxygen occurred.…”
Section: Applicationsmentioning
confidence: 99%